Are self-perceptions of ageing modifiable? Examination of an exercise programme with vs. without a self-perceptions of ageing-intervention for older adults. Issue 6 (3rd June 2019) - Beyer, Ann-Kristin; Wolff, Julia K.; Freiberger, Ellen; Wurm, Susanne
Abstract: Objective: Longitudinal studies have consistently shown beneficial effects of positive self-perceptions of ageing (SPA) on health. However, SPA are more often negative than positive, particularly in older adults. For this reason, the present study tested the effectiveness of an intervention to promote more positive SPA in the context of an exercise programme for older adults. Design: Eighty-four community-dwelling older adults (66-88 years; M (SD)=76.8(5.29)) were randomly assigned to a group-based exercise programme over 12 weeks with ( n  = 46) or without ( n  = 38) a psychological intervention to change SPA, consisting of four intervention units over the programme period. Main Outcome Measures: A gain- and a loss-related domain of SPA were assessed at baseline, after the first half of the programme, directly after the programme and in a follow-up four weeks later. Results: Latent change score models showed an improvement of participants' SPA in the intervention group in both SPA domains after the programme, whereas SPA did not change in the control group. Both groups showed an improvement in physical performance, however, only the IG showed additional improvements in mental health. Conclusion : The implementation of an SPA intervention is a promising approach in regular health promotion programmes for older adults.